(untitled) (International Journal of Engineering and Computer Science, 2015)
In wireless sensor networks, energy efficiency is one of the most powerful factor. In wireless sensor networks, energy consumption can be occur in various forms and states like receiving, idle, transmitting and sleeping state energy consumptions. This is the reason, why implementation of energy efficiency model becomes important and energy model considered as a resource constraints. In this research, we implemented energy efficiency model for Sensor-MAC, which is a medium access control (MAC) layer protocol in wireless sensor network (WSN). We’ve traced energy consumption in four different states of network that includes sleep state, receive state, transmitting state and idle state. We further calculated average energy consumption for all states. We added energy breakdown in each state to support detailed energy analysis. We calculated average energy consumption in all states by taking different number of nodes and making different numbers of connection between them in WSN and have a conclusion that when we increase number of connections in a WSN, for the SMAC protocol the energy consumption is also increases. We also noticed energy consumption in network when the network has no connection between nodes.